(untitled) (World Economics and Finance Bulletin, 2025)
This research aims to study the role of digital transformation in the development of the Iraqi banking system, with a focus on the experience of Trust Bank as a case study. Digital transformation is one of the key factors that contribute to improving the efficiency of banking operations, providing innovative financial services, and enhancing financial inclusion. The research discusses the impact of the application of financial technology, such as online and mobile banking, on improving the quality of services and increasing customer satisfaction. It also addresses the challenges facing Iraqi banks in embracing digital transformation, such as technological infrastructure, regulatory and security challenges. The study found that digital transformation plays a pivotal role in the development of the Iraqi banking sector, but requires clear strategies and sustainable investments to ensure its success.